Antimicrobial Potential and Biochemical Profile of Methanolic Extracts of Common Solanum Species in Nigeria - Adepoju, Abiola Grace Femi; Adepoju, Adeyinka Olufemi; Oni, Solomon Oluwasunmibare (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Due to the rise in microbial resistance to orthodox medicines, there is need for investigation towards the discovery of plants with potential pharmacological effects. Methanolic extracts of the leaves of four Solanum species were screened for their antimicrobial properties and for various biochemical analyses, using standard methods. S. melongena showed highest antifungal activity against Aspergillus niger and Aspergillus flavus. The antifungal activity of S. gilo extract was the highest at 5 mg/ml against Aspergillus flavus and Candida albicans. Antifungal activity of S. macrocarpon extract was observed as the highest at 25 mg/ml against Candida albicans. The promising antimicrobial potential of the investigated plants can be attributed to the presence of specific biochemical compounds detected in them by means of GC-MS profiling and other biochemical analyses. The study revealed that the four species of African eggplant are nutritionally and therapeutically valuable and can be further developed into medicinal products. Dhaka Univ. J. Pharm. Sci. 22(2): 163-172, 2023 (December)